2010
DOI: 10.1021/bi1000849
|View full text |Cite
|
Sign up to set email alerts
|

Specific High-Affinity Binding of Thiazole Orange to Triplex and G-Quadruplex DNA

Abstract: Interaction of Thiazole Orange (TO) with double-, triple-, and quadruple-stranded forms of DNA was studied. We have demonstrated by UV-vis absorption, circular dichroism (CD), and fluorescence spectroscopy that TO binds with much higher affinity to triplex and G-quadruplex DNA structures compared to double-stranded (ds) DNA. Complexes of the dye with DNA triplexes and G-quadruplexes are very stable and do not dissociate during chromatography and gel electrophoresis. TO binding to either triple- or quadruple-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
136
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(147 citation statements)
references
References 51 publications
9
136
0
2
Order By: Relevance
“…Thiazole orange (TO) is generally used as a DNA-bound intercalator. Initial studies have demonstrated that thiazole orange binds to the quadruplex-forming oligonucleotide with high affinity [23,24]. In this investigation, TO was used for fluorescent intercalator displacement assay.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…Thiazole orange (TO) is generally used as a DNA-bound intercalator. Initial studies have demonstrated that thiazole orange binds to the quadruplex-forming oligonucleotide with high affinity [23,24]. In this investigation, TO was used for fluorescent intercalator displacement assay.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…[10][11][12][13][14][15] Pyrimidine TFOs labeled with thiazole orange (TO) exhibited comparably larger changes in fluorescence intensities before and after triplex formation 14,15 because the fluorescence intensity of TO molecules is low in the presence of poly-pyrimidine singlestranded DNA 16 and high in the presence of DNA triplexes. 15,17 To suppress the fluorescence of the TO molecules covalently attached to DNA oligonucleotides, the utilization of excitonic interaction between two molecules of TO is effective. 18,19 Exciton theory explains that the fluorescence of two dye molecules forming an H-dimer is strongly suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32] ECHO probes emitting low background fluorescence were expected to be also applicable to detect double-stranded DNA as TO molecules emit intense fluorescence in the presence of DNA triplexes. 15,17 However, DNA triplexes formed by ECHO probes have not been reported and the photophysical properties are unknown. Besides the photophysical properties, the effects on the thermal stability and kinetic parameters of the DNA triplexes formed by the ECHO probes, which are caused by the interaction of the two TO molecules with the DNA triplexes, are also important, because DNA triplexes intrinsically have a low thermal stability and slow formation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Poly-G DNA was not considered here, since they tend to form G-quadruplex and emit very strongly with TO. 43 TO is a useful dye for staining the A-motif if G-quadruplex can be excluded. We then tested the response of TO with DNA 1-4.…”
mentioning
confidence: 99%